2015
DOI: 10.1086/680189
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Functional Significance of Ca2+‐Activated Cl Channels in Pulmonary Arterial Smooth Muscle

Abstract: Increased peripheral resistance of small distal pulmonary arteries is a hallmark signature of pulmonary hypertension (PH) and is believed to be the consequence of enhanced vasoconstriction to agonists, thickening of the arterial wall due to remodeling, and increased thrombosis. The elevation in arterial tone in PH is attributable, at least in part, to smooth muscle cells of PH patients being more depolarized and displaying higher intracellular Ca 2+ levels than cells from normal subjects. It is now clear that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 285 publications
(882 reference statements)
2
47
0
Order By: Relevance
“…1), multiple members of five classes from the transient receptor potential (TRP) family of ion channels (Table 4, Fig. 1), two or more classes of Cl − channels (184, 303, 304, 584, 632, 829, 956, 957) and members of the epithelial Na + /acid-sensing channel (ENaC) (340342, 460, 502, 510, 698, 697, 1465). This review will focus on VGCCs, K + channels, ER Ca 2+ release channels and TRP channels that contribute to myogenic and agonist-modulated tone in vascular SMCs of resistance arteries and arterioles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1), multiple members of five classes from the transient receptor potential (TRP) family of ion channels (Table 4, Fig. 1), two or more classes of Cl − channels (184, 303, 304, 584, 632, 829, 956, 957) and members of the epithelial Na + /acid-sensing channel (ENaC) (340342, 460, 502, 510, 698, 697, 1465). This review will focus on VGCCs, K + channels, ER Ca 2+ release channels and TRP channels that contribute to myogenic and agonist-modulated tone in vascular SMCs of resistance arteries and arterioles.…”
Section: Introductionmentioning
confidence: 99%
“…This review will focus on VGCCs, K + channels, ER Ca 2+ release channels and TRP channels that contribute to myogenic and agonist-modulated tone in vascular SMCs of resistance arteries and arterioles. Chloride channels (184, 303, 304, 584, 632, 829, 956, 957) and ENaC (340342, 460, 502, 510, 698, 697, 1465) that may contribute to myogenic- and agonist-induced tone of some resistance arteries and arterioles will not be discussed. Ion channel function in the pulmonary circulation also will not be reviewed in detail (937).…”
Section: Introductionmentioning
confidence: 99%
“…These conditions are favorable to the sustained efflux of Cl − and influx of Ca 2+ into the cell. 33,43 Our results suggest that, during capacitation, Cl − could also promote sustained Ca 2+ uptake because the [Cl − ]i (∼58 mM) and the equilibrium potential for Cl − (−22 mV) were similar, and also that the inhibition of TMEM16A by T16Ainh-A01 alters both the equilibrium potential of Cl − and the plasma membrane potential such that Ca 2+ uptake decreases ( Figure 7B). It has also been suggested that the increased activity of an important complex of different transporters, CFTR/ SLC26A3/SLC26A6/sNHE (Na + /H + exchangers), could directly increase [Cl − ]i during capacitation, allowing HCO 3 − uptake and maintaining the high intracellular concentrations of cAMP needed for capacitation processes.…”
Section: Discussionmentioning
confidence: 78%
“…Several studies have compared the specificity of NFA with that of T16Ainh‐A01, and despite arguments against such specificity, both NFA, and T16Ainh‐A01 block Cl − currents produced by TMEM16A . Therefore, T16Ainh‐A01 and NFA are considered traditional and potent TMEM16A blockers and are frequently used to investigate the physiological function of these Cl − channels on tissues or cells . For these reasons, we analyzed the role of TMEM16A by blocking the activity of the channels using both T16Ainh‐A01 and NFA, assuming that blocking Cl − currents would affect the normal behavior of the sperm.…”
Section: Discussionmentioning
confidence: 99%
“…In olfactory and vomeronasal sensory neurons, CaCCs mediate a large component of transduction current [25] and in other neuronal cell types they can control excitability [6]. Moreover, they regulate the fluid transport in different types of epithelia [7] and modulate the activity of smooth muscles of the blood vessels [8,9]. …”
Section: Introductionmentioning
confidence: 99%